Polymer base material and preparation method thereof, composite current collector, electrode plate and lithium ion battery

By applying a polyurea resin coating on the surface of the polymer film, the problems of insufficient peeling of conductive layers and heat resistance in the composite fluid collection are solved, and the circulation performance and service life of lithium-ion batteries are improved.

CN119241886APending Publication Date: 2025-01-03ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411367634.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The thermal resistance and weak mechanical properties of the polymer films in the existing composite liquids lead to a reduced safety performance and cycling performance of lithium-ion batteries, and the bonding force between the conductive layer and the polymer film is low, which easily leads to peeling of the conductive layer. , affects the energy density and service life of the battery.

Method used

A polyurea resin coating is provided on the surface of the polymer film material, and the reaction of isocyanate and amine-based compounds in the solvent is formed to improve the binding force and mechanical properties of the polymer substrate and the conductive layer, and enhance heat resistance and chemical stability.

Benefits of technology

It effectively improves the bonding force between polymer substrate and conductive layer, avoids the peeling of conductive layer, extends the circulation capacity and service life of the battery, and improves the safety performance and production efficiency of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241886A_ABST
    Figure CN119241886A_ABST
Patent Text Reader

Abstract

The invention provides a polymer base material and a preparation method thereof, a composite current collector, an electrode plate and a lithium ion battery, and belongs to the field of lithium ion battery materials. The polymer base material for the composite current collector comprises a polymer membrane material and a coating, the coating is arranged on at least one surface of the polymer membrane material, the main component of the coating is polyurea resin, the polyurea resin is formed by reaction of a first component and a second component in a solvent, the main component of the first component is isocyanate, and the main component of the second component is an amino compound. The polyurea resin coating is arranged on the polymer membrane material, so that the binding force of the polymer base material and the conductive layer is improved, the heat resistance, the mechanical property and the chemical stability of the composite current collector are improved, and the cycle performance, the safety, the service life and the like of the lithium ion battery are further improved. The problems that a conducting layer in an existing composite current collector is prone to falling off, a composite current collector base film is prone to corrosion and thermal damage, and then the cycle performance, safety and service life of a lithium battery are reduced are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion battery materials, and in particular to a polymer substrate and a preparation method thereof, a composite current collector, an electrode sheet and a lithium ion battery. Background Art

[0002] As an important component of lithium-ion batteries, current collectors play the role of collecting current and carrying negative electrode active materials. Their performance is directly related to the cycle life, energy density, safety performance, etc. of lithium-ion batteries. Traditional metal foil current collectors such as copper foil or aluminum foil have disadvantages such as large weight and high cost, which make it difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, composite current collectors have been developed in recent years. A metal layer with a thickness of about 1 micron is set on the upper and lower surfaces of polymer film materials such as polyethylene terephthalate film (PET film), biaxially oriented polypropylene film (BOPP film) or polyimide film (PI film). Compared with traditional metal foil current collectors, composite current collectors have the advantages of high conductivity, low cost and light weight.

[0003] However, in the existing composite current collector, the polymer film material still has at least the following technical problems: the polymer film material (such as BOPP film, etc.) has poor heat resistance, and is easily aged by heat during the use of the composite current collector, thereby reducing the safety performance and cycle performance of the lithium-ion battery, and the mechanical properties are also relatively weak. After the composite current collector is prepared, the mechanical properties will further decay, resulting in the composite current collector When coating the electrode material, only a very slow speed can be used, otherwise there is a risk of breaking the belt, affecting production efficiency and increasing costs; although some polymer film materials (such as PET film, etc.) have the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of composite copper foil and negative electrode materials, the chemical properties of this type of polymer film material are unstable, unstable in the electrolyte, and easily degraded and corroded, resulting in the composite current collector After the lithium-ion battery is assembled, the cycle capacity decay is serious and the cycle life is very short; and the bonding force between the conductive layer and the polymer film material in the existing composite current collector is generally low, which easily causes the risk of the conductive layer peeling or falling off from the polymer film material, thereby affecting the energy density and service life of the lithium-ion battery.

[0004] Therefore, how to propose a polymer substrate and its preparation method, a composite current collector, an electrode sheet and a lithium-ion battery that can improve the comprehensive performance of the composite current collector to solve or at least alleviate at least one of the above technical problems is a problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above-mentioned technical problems, the present invention provides a polymer substrate and a preparation method thereof, a composite current collector, an electrode sheet and a lithium-ion battery to solve or at least alleviate at least one technical problem existing in the above-mentioned polymer substrate and the technical problems caused by the composite current collector, the electrode sheet and the lithium-ion battery.

[0006] According to a specific embodiment of the present invention, in a first aspect, the present invention provides a polymer substrate for a composite current collector, comprising a polymer film material and a coating, wherein the coating is arranged on at least one surface of the polymer film material, wherein a main component of the coating is a polyurea resin, and the polyurea resin is formed by reacting a first component and a second component in a solvent, wherein a main component of the first component is an isocyanate, and a main component of the second component is an amino compound, and the solvent is used to dissolve the first component and the second component, and the mass ratio of the first component, the second component and the solvent is 10 to 35:8 to 35:30 to 82.

[0007] Optionally, the isocyanate includes one or more of diphenylmethane diisocyanate, toluene diisocyanate and polyether-modified isocyanate.

[0008] Optionally, the amino compound includes one or more of polyetheramine, polyesteramine and modified amine compounds.

[0009] Optionally, the solvent includes one or more of ethyl acetate, butyl acetate, dimethylformamide, and toluene.

[0010] Optionally, the mass ratio of the first component, the second component and the solvent is 25-35:23-35:30-52.

[0011] Optionally, the solid content of the first component is 30% to 65%.

[0012] Optionally, the solid content of the second component is 30% to 65%.

[0013] Optionally, the coating has a thickness of 0.5 to 10 microns.

[0014] Optionally, the polymer film material is a polyethylene terephthalate (PET) film.

[0015] According to a specific embodiment of the present invention, in a second aspect, the present invention provides a method for preparing a polymer substrate for a composite current collector as described above, comprising the following steps:

[0016] Step (S1), mixing the first component and the second component to obtain a mixture, and stirring the mixture at a high speed;

[0017] Step (S2), adding the solvent to the mixed material, adjusting the solid content to 15% to 35%, and adjusting the viscosity to below 500 cps, to form a slurry; and

[0018] Step (S3), coating the slurry on at least one surface of the polymer film material, and drying, to form the coating on at least one surface of the polymer film material.

[0019] Optionally, in the step (S1), during the high-speed stirring to form the mixed material, the temperature of the mixed material and the stirring are controlled to be 10 to 35°C.

[0020] Optionally, the high-speed stirring time is 20 to 40 minutes.

[0021] According to a specific embodiment of the present invention, in a third aspect, the present invention provides a composite current collector, comprising a polymer substrate and a conductive layer, wherein the polymer substrate is a polymer substrate for a composite current collector as described in any one of the above items, or a polymer substrate for a composite current collector obtained by any of the preparation methods described in the above items, and the conductive layer is arranged on a surface of the coating away from the polymer film material.

[0022] According to a specific embodiment of the present invention, in a fourth aspect, the present invention provides an electrode sheet, comprising a current collector and an electrode membrane, wherein the electrode membrane is arranged on the surface of the current collector, and the current collector adopts any composite current collector as described above.

[0023] According to a specific embodiment of the present invention, in a fifth aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet adopts the electrode sheet as described above.

[0024] Compared with the prior art, the above solution of the embodiment of the present invention has at least the following beneficial effects:

[0025] (1) In the polymer substrate of the present invention, a coating whose main component is a polyurea resin is disposed on the surface of the polymer film material. The polyurea resin coating is rich in polar groups. After the polymer substrate of the present invention is used for the composite current collector, the bonding force between the polymer substrate and the conductive layer can be effectively improved, thereby avoiding or at least alleviating the peeling and shedding of the conductive layer during the use of the composite current collector, reducing the cycle capacity of the lithium ion battery, and thus increasing the energy density and service life of the composite current collector and the lithium ion battery; and the polarity of the polyurea group in the coating is very large, and a large number of hydrogen bonds can be formed, which has excellent heat resistance and mechanical properties, and can improve the mechanical properties and heat resistance of the polymer substrate. The high heat resistance can avoid or at least alleviate the thermal aging of the composite current collector during use. The safety performance and cycle performance of the lithium-ion battery are thereby improved, and the coating can also alleviate the thermal damage to the polymer film material during the process of evaporating the conductive layer; the higher mechanical properties can increase the speed of the composite current collector when coating the electrode material, thereby improving production efficiency and reducing costs; in addition, the polyurea resin in the coating has good chemical stability and can be used in strong acid and strong alkali environments, and the coating formed by the polyurea resin is continuous and seamless, which can effectively block acidic substances from penetrating into the polymer substrate, and can alleviate the corrosion of the polymer film material in the composite current collector by the electrolyte, ensuring that the composite current collector can maintain a stable structure even if it is immersed in the electrolyte for a long time, thereby solving the problem of reduced battery cycle capacity and increasing the service life of the composite current collector and the lithium-ion battery.

[0026] (2) In the method for preparing the polymer substrate for the composite current collector of the present invention, the equipment for preparing the coating is simple, low-cost, and easy to operate, which is conducive to the large-scale production and application of the polymer substrate for the composite current collector, and meets the demand for efficient and low-cost production methods in the field of coating preparation technology; and the energy consumption is low, which is in line with the current trend of green development and meets the new demand for environmental protection and energy saving in the field of composite material science. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings herein are incorporated into and constitute a part of the specification, showing embodiments consistent with the present invention, and together with the specification, are used to explain the principles of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0028] Figure 1 A schematic diagram of the structure of a polymer substrate for a composite current collector provided in an embodiment of the present invention;

[0029] Figure 2 A flow chart of a method for preparing a polymer substrate for a composite current collector provided in an embodiment of the present invention;

[0030] Figure 3 A schematic diagram of the structure of a composite current collector provided in an embodiment of the present invention.

[0031] The reference numerals in the specific implementation manner are as follows:

[0032] Polymer substrate 1, polymer film material 11, coating layer 12; composite current collector 20, conductive layer 2. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0035] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0036] In the description of the embodiments of the present invention, the orientations or positional relationships indicated by technical terms such as "upper", "lower", and "thickness" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present invention and simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present invention.

[0037] In the description of the embodiments of the present invention, the term "and / or" used is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] In the description of the embodiments of the present invention, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.

[0039] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0040] The composite current collector is usually a sandwich structure, with the middle layer being a polymer film such as PET / BOPP / PI, and the upper and lower surfaces being metal conductive layers with a thickness of about 1 micron. Compared with traditional metal foil current collectors, composite current collectors have the advantages of high conductivity, low cost, and light weight.

[0041] However, the inventors have found through research that in the existing composite current collectors, the polymer film materials still have at least the following technical problems: the polymer film materials (such as BOPP films, etc.) have poor heat resistance, and are easily aged by heat during the use of the composite current collector, thereby reducing the safety performance and cycle performance of the lithium-ion battery, and the mechanical properties are also relatively weak. After the composite current collector is prepared, the mechanical properties will further decay, resulting in the composite current collector When coating the electrode material, only a very slow speed can be used, otherwise there is a risk of breaking the belt, affecting production efficiency and increasing costs; although some polymer film materials (such as PET films, etc.) have the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of composite copper foil and negative electrode materials, the chemical properties of such polymer film materials are unstable, unstable in the electrolyte, and easily degraded and corroded, resulting in the composite current collector After the lithium-ion battery is assembled, the cycle capacity decay is serious and the cycle life is very short; and the adhesion between the conductive layer and the polymer film material in the existing composite current collector is generally low, which easily causes the risk of the conductive layer peeling or falling off from the polymer film material, thereby affecting the energy density and service life of the lithium-ion battery.

[0042] In order to solve or at least alleviate the above-mentioned technical problems, the present invention considers applying a coating on the surface of a polymer film material, and through a large number of experiments and studies, it is concluded that setting a coating whose main component is a polyurea resin on the surface of the polymer film material can improve the mechanical properties, heat resistance and chemical stability of the polymer film material and the composite current collector prepared therefrom in the electrolyte, and increase the adhesion between the polymer film material and the conductive layer and other properties, thereby reducing the cycle capacity attenuation of the lithium-ion battery, and improving the safety performance, cycle performance and service life of the lithium-ion battery.

[0043] Specifically, an embodiment of the present invention provides a polymer substrate for a composite current collector, including a polymer film material and a coating, wherein the coating is arranged on at least one surface of the polymer film material, and a main component of the coating is a polyurea resin, and the polyurea resin is formed by reacting a first component and a second component in a solvent, wherein a main component of the first component is an isocyanate, and a main component of the second component is an amino compound, and the solvent is used to dissolve the first component and the second component, and the mass ratio of the first component, the second component and the solvent is 10 to 35:8 to 35:30 to 82.

[0044] In the polymer substrate of the present invention, a coating whose main component is a polyurea resin is arranged on the surface of the polymer film material, and the polyurea resin coating is rich in polar groups. After the polymer substrate of the present invention is used for the composite current collector, the bonding force between the polymer substrate and the conductive layer can be effectively improved, and the peeling and shedding of the conductive layer of the composite current collector during use can be avoided or at least alleviated, and the problem of reducing the cycle capacity of the lithium ion battery can be reduced, thereby increasing the energy density and service life of the composite current collector and the lithium ion battery; and the polarity of the polyurea group in the coating is very large, and a large number of hydrogen bonds can be formed, and the coating has excellent heat resistance and mechanical properties, which can improve the mechanical properties and heat resistance of the polymer substrate, and the higher heat resistance can avoid or at least alleviate the thermal aging of the composite current collector during use, thereby improving the mechanical properties and heat resistance of the polymer substrate. The safety and cycle performance of lithium-ion batteries are improved, and the coating can also alleviate the thermal damage of the polymer film material during the evaporation of the conductive layer; the higher mechanical properties can increase the speed of the composite current collector when coating the electrode material, improve production efficiency and reduce costs; in addition, the chemical stability of the polyurea resin in the coating is good, and it can be used in a strong acid and strong alkali environment, and the coating formed by the polyurea resin is continuous and seamless, which can effectively block the acidic substances from penetrating into the polymer substrate, and can alleviate the corrosion of the polymer film material in the composite current collector by the electrolyte, ensuring that the composite current collector can maintain a stable structure even if it is immersed in the electrolyte for a long time, thereby solving the problem of reduced battery cycle capacity and improving the service life of the composite current collector and lithium-ion batteries. In addition, the mass fraction ratio of the first component, the second component and the solvent is 10-35:8-35:30-82, ensuring that the molar ratio of the isocyanate group and the amine group is about 1:1, so that the reaction is complete, and then the incomplete reaction can be avoided, resulting in the degradation of the mechanical properties and chemical stability of the coating after film formation.

[0045] The optional embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0046] See also Figure 1According to some embodiments of the present invention, the present invention provides a polymer substrate 1 for a composite current collector, comprising: a polymer film material 11 and a coating 12, wherein the coating 12 is disposed on the upper surface and the lower surface of the polymer film material 11. It can be understood that in some other embodiments, the coating 12 may also be disposed only on the upper surface or the lower surface of the polymer film material 11.

[0047] The main component of the coating 12 is polyurea resin, which is formed by the reaction of a first component and a second component. In some preferred embodiments, the component of the coating 12 is polyurea resin.

[0048] The main component of the first component is isocyanate. In some preferred embodiments, the first component is isocyanate. The isocyanate is preferably a modified isocyanate. In some embodiments, the isocyanate is one or more of diphenylmethane diisocyanate, toluene diisocyanate, and polyether-modified isocyanate. The above-mentioned isocyanates, especially polyether-modified isocyanates, have a stable structure and can improve the chemical resistance of the coating; have a lower viscosity, which is conducive to material mixing and coating; have good strength and toughness, and can extend the service life of the composite current collector in the battery cell; have good heat resistance, and improve the tolerance of the polymer base film during physical vapor deposition (PVD) process.

[0049] The main component of the second component is an amine compound. In some preferred embodiments, the second component is an amine compound. The amine compound is preferably a modified amine compound. In some embodiments, the amine compound is one or more of polyetheramine, polyesteramine and modified amine compounds. The above-mentioned amine compounds, especially modified amine compounds, have a stable structure and can improve the chemical resistance of the coating; have a lower viscosity, which is conducive to material mixing and coating; have better strength and toughness, and can extend the service life of the composite current collector in the battery cell; have better heat resistance, and improve the tolerance of the polymer base film during physical vapor deposition (PVD) process.

[0050] Too high or too low material viscosity will lead to uneven mixing of materials in the later stage and unstable film formation. Materials with high solid content have high viscosity, and materials with low solid content have low viscosity. In some embodiments, the solid content of the first component is 30% to 65%, and the solid content of the second component is 30% to 65%. The viscosity of the first component and the second component in this solid content range is moderate, so that the materials are mixed evenly in the later stage and the film formation is stable.

[0051] The solvent is used to dissolve the first component and the second component. In some embodiments, the solvent may be, but is not limited to, one or more of ethyl acetate, butyl acetate, dimethylformamide, and toluene.

[0052] The mass fraction ratio of the first component, the second component and the solvent is 10-35:8-35:30-82, and this mass fraction range ensures that the molar ratio of the isocyanate group and the amine group is about 1:1, so that the reaction is complete, thereby avoiding incomplete reaction, which leads to deterioration of the mechanical properties and chemical resistance of the coating after film formation. In some preferred embodiments, the mass fraction ratio of the first component, the second component and the solvent is 25-35:23-35:30-52.

[0053] The main component of the coating 12 is polyurea resin. The polyurea resin coating is rich in polar groups, which can effectively improve the bonding force between the polymer film material 11 and the conductive layer. The polarity of the polyurea group is very large, and a large number of hydrogen bonds can be formed. It has excellent heat resistance and mechanical properties. Coating it on the surface of the polymer film material 11 can improve the mechanical properties and heat resistance of the polymer 1, and can also alleviate the thermal damage to the polymer film material during the subsequent evaporation of the conductive layer. In addition, the chemical stability of the polyurea resin is good and can be used in strong acid and alkali environments. The coating 12 formed by the polyurea resin is continuous and seamless, which can effectively prevent acidic substances from penetrating into the polymer film material 11. When used as a composite current collector, it can alleviate the corrosion of the electrolyte to the polymer film material, ensuring that the composite current collector can maintain a stable structure even if it is immersed in the electrolyte for a long time, thereby improving the service life of the composite current collector.

[0054] If the thickness of the coating 12 is too large, the volume and mass of the lithium-ion battery will increase, and the energy density of the lithium-ion battery will be reduced; if the thickness of the coating 12 is too small, the coating 12 cannot form a dense protective layer, and the protection ability of the polymer film material 11 is insufficient; and the improvement of the chemical stability and heat resistance of the polymer film material 11 is insufficient. In some embodiments, the thickness of the coating 12 is 0.5 to 10 microns.

[0055] In some embodiments, the polymer film material 11 is a polyethylene terephthalate film (PET film). The PET film has the characteristics of low cost, excellent mechanical properties, and good thermal stability, and can be well adapted to the processing technology of composite copper foil and negative electrode materials. After the PET film is coated with the coating 12, the embodiment of the present invention further improves the mechanical properties and heat resistance of the PET film; it can also improve the chemical stability of the PET film, so that the PET film is stable in the electrolyte and is not degraded or corroded; and when preparing the composite current collector, it can also improve the adhesion between the conductive layer and the PET film to prevent the conductive layer from peeling off or falling off from the PET film.

[0056] It is understandable that the polymer film material 11 of the present invention is not limited to the PET film. In some other embodiments, it can also be a BOPP film (biaxially oriented polypropylene film), a polyimide film (PI film) or other commonly used polymer film materials for composite current collectors.

[0057] See also Figure 2 According to some embodiments of the present invention, the present invention further provides a method for preparing the polymer substrate 1 for a composite current collector as described above, comprising the following steps:

[0058] Step (S1), mixing the first component and the second component to obtain a mixture, and stirring the mixture at a high speed;

[0059] Step (S2), adding the solvent to the mixed material, adjusting the solid content to 15% to 35%, and adjusting the viscosity to below 500 cps, to form a slurry; and

[0060] Step ( S3 ), coating the slurry onto the surface of the polymer film material 11 , and drying, to form the coating layer 12 on the surface of the polymer substrate 1 .

[0061] The first group of second components and the solvent are the same as those described in the above embodiments, including all the technical features described in the above embodiments, which will not be repeated here.

[0062] The mass ratio of the first component, the second component and the solvent is 10 to 35: 8 to 35: 30 to 82. In some preferred embodiments, the mass ratio of the first component, the second component and the solvent is 25 to 35: 23 to 35: 30 to 52.

[0063] In some embodiments, in step (S1), during the high-speed stirring of the mixed material, the temperature of the mixed material and the stirring are controlled to be 10 to 35°C to avoid premature reaction of the material due to the stirring temperature rise, which affects the open period, that is, the period from the mixing of the slurry to the slurry deteriorating and unusable. The high-speed stirring time can be selected according to actual conditions. In some embodiments, the high-speed stirring is 20 to 40 minutes. In this embodiment, during the high-speed stirring of the mixed material, the temperature of the mixed material and the stirring is controlled to be 30°C, and the high-speed stirring is performed for 30 minutes.

[0064] In some embodiments, in step (S2), the solid content is adjusted to 15% to 35% and the viscosity is ≤500cps. The slurry in this solid content and viscosity range can match a faster coating speed and has better coating uniformity and stability. In some preferred embodiments, the solid content of the slurry is adjusted to 30%.

[0065] In some embodiments, in step (S3), the method of coating the slurry onto the surface of the polymer film 11 includes but is not limited to roller coating, spray coating, flow coating or dip coating.

[0066] The drying method may be drying or natural drying according to actual conditions. In some embodiments, the drying method is drying.

[0067] The equipment for preparing the coating in the preparation method of the polymer substrate 1 for the composite current collector is simple, low-cost, and easy to operate, which is conducive to the large-scale production and application of the polymer substrate for the composite current collector, and meets the demand for efficient and low-cost production methods in the field of coating preparation technology; and it has low energy consumption, which is in line with the current trend of green development and meets the new demand for environmental protection and energy saving in the field of composite material science.

[0068] See also Figure 3 According to some embodiments of the present invention, the present invention further provides a composite current collector 20, comprising the polymer substrate 1 and a conductive layer 2, wherein the conductive layer 2 is disposed on the surface of the polymer substrate 1, specifically, disposed on the surface of the coating 12 in the polymer substrate 1 away from the surface of the polymer film material 11.

[0069] In some embodiments, the composite current collector 20 is a positive electrode current collector, and the conductive layer 2 can be a common conductive layer of a positive electrode current collector, which can be, but not limited to, a metal aluminum layer or a composite aluminum layer, etc. In some other embodiments, the composite current collector 20 is a negative electrode current collector, and the conductive layer 2 can be a common conductive layer of a negative electrode current collector, which can be, but not limited to, a metal copper layer, a composite copper layer, etc. In this embodiment, the composite current collector 20 is a negative electrode current collector, and the conductive layer 2 is a metal copper layer.

[0070] The conductive layer 2 can be deposited on the surface of the polymer substrate 1 by at least one of vacuum evaporation, ion plating, radio frequency sputtering, magnetron sputtering or reactive sputtering, but is not limited to. Preferably, the conductive layer 2 is formed on the surface of the coating 12 by vacuum evaporation.

[0071] The composite current collector 20 of the embodiment of the present invention is provided with a coating 12 whose main component is a polyurea resin between the polymer film material 11 and the conductive layer 2, so that the bonding force and mechanical properties between the polymer film material 11 and the conductive layer 2 are greatly improved, which can avoid the problem of battery cycle capacity drop caused by the shedding of the conductive layer 2 when the composite current collector 20 is used in a lithium-ion battery, improve the performance and service life of the battery, and meet the demand for high-performance lithium-ion batteries in the battery manufacturing field. In addition, the heat resistance and corrosion resistance of the composite current collector 20 are also improved, thereby improving the stability of the composite current collector 20 in the electrolyte, alleviating the aging of the composite current collector, extending the service life, and thus improving the cycle performance of the lithium-ion battery.

[0072] According to some embodiments of the present invention, the present invention provides an electrode sheet, comprising the composite current collector 20 as described above and an electrode film material disposed on the surface of the composite current collector 20. The electrode sheet may be a positive electrode sheet or a negative electrode sheet.

[0073] According to some embodiments of the present invention, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and at least one of the positive electrode sheet and the negative electrode sheet adopts the electrode sheet, that is, the current collector in the electrode sheet adopts the composite current collector 20.

[0074] The preparation process, test methods and test data of the embodiments and comparative examples are introduced below:

[0075] Embodiment 1:

[0076] The preparation of the polymer substrate comprises the following steps:

[0077] Step (S1), according to the weight parts, 25 parts of polyether modified isocyanate (model: AMT-DI-03) and 23 parts of modified linear fatty amine (model: AMT-PA-05) are mixed, the mixing and stirring temperature is controlled to be 10-35° C., and the mixture is stirred at a high speed for 30 minutes to form a mixed material, wherein the solid content of AMT-DI-03 is 65%, and the solid content of AMT-PA-05 is 60%;

[0078] Step (S2), adding 52 parts of butyl acetate to the mixture, adjusting the viscosity to below 500 cps, and adjusting the solid content to 30%, to form a slurry; and

[0079] Step (S3), coating the slurry onto the surface of the PET film, drying it, and rolling it up for later use.

[0080] The preparation of the composite current collector comprises the following steps:

[0081] A copper layer is deposited on the surface of the polymer substrate obtained in the above step (S3). Specifically, the copper layer is deposited on the surface of the coating away from the PET film material by a vacuum evaporation method.

[0082] Embodiment 2:

[0083] The preparation of the polymer substrate comprises the following steps:

[0084] Step (S1), according to parts by mass, 30 parts of a mixture of hexamethylene diisocyanate (model: AMT-DI-08) and polyether modified isocyanate (model: AMT-DI-03) (mixing ratio of 1:1, solid content of 57.3%) and 30 parts of a mixture of aromatic amine and linear fatty amine (model: AMT-PA-13, solid content of 48.8%) are mixed, the mixing and stirring temperature is controlled to be 10-35° C., and high-speed stirring is performed for 30 minutes to form a mixed material;

[0085] Step (S2), adding 40 parts of a mixed solvent of ethyl acetate and butyl acetate (ethyl acetate:butyl acetate=2:3) to the mixture, adjusting the viscosity to below 500 cps, and adjusting the solid content to 31.8% to form a slurry; and

[0086] Step (S3), coating the slurry onto the surface of the PET film, drying it, and rolling it up for later use.

[0087] The preparation of the composite current collector comprises the following steps:

[0088] A copper layer is deposited on the surface of the polymer substrate obtained in the above step (S3). Specifically, the copper layer is deposited on the surface of the coating away from the PET film material by a vacuum evaporation method.

[0089] Embodiment 3:

[0090] The preparation of the polymer substrate comprises the following steps:

[0091] Step (S1), according to parts by mass, 33 parts of a mixture of isophorone diisocyanate (model: AMT-DI-12) and polyether modified isocyanate (model: AMT-DI-03) (mixing ratio 1:2, solid content 47.2%) and 30 parts of a mixture of heterocyclic amine and linear fatty amine (model: AMT-PA-11, solid content 42.1%) are mixed, the mixing and stirring temperature is controlled to be 10-35° C., and high-speed stirring is performed for 30 minutes to form a mixed material;

[0092] Step (S2), adding 37 parts of xylene to the mixed material, adjusting the viscosity to below 500 cps, and adjusting the solid content to 34.6%, to form a slurry; and

[0093] Step (S3), coating the slurry onto the surface of the PET film, drying it, and rolling it up for later use.

[0094] The preparation of the composite current collector comprises the following steps:

[0095] A copper layer is deposited on the surface of the polymer substrate obtained in the above step (S3). Specifically, the copper layer is deposited on the surface of the coating away from the PET film material by a vacuum evaporation method.

[0096] Comparative Example 1:

[0097] The polymer substrate is a PET film material without coating. The composite current collector is directly obtained by vacuum evaporating a copper layer on the PET film material.

[0098] The composite current collectors obtained in Examples 1-3 and Comparative Example 1 were used as negative current collectors to assemble button-type half-cells. Except for the different negative current collectors, the other components were the same. The positive electrode of the battery used lithium iron phosphate, the negative electrode used graphite, and the electrolyte used Hairong 9212 electrolyte.

[0099] The adhesion of the copper layer on the PET film in the composite current collector obtained in Examples 1-3 and Comparative Example 1, the adhesion of the copper layer on the PET film after the composite current collector is immersed in 85°C Hairong 9212 electrolyte for 3 days, the thermal shrinkage of the composite current collector at 150°C for 30 minutes, and the number of cycle cycles of the button half-battery assembled with the composite current collector in Examples 1-3 and Comparative Example 1 when the charge and discharge rate is 1C and the battery capacity decays to 80% are tested respectively. The test results are shown in Table 1.

[0100] Table 1 Test data of Examples 1-3 and Comparative Example 1

[0101]

[0102] From the comparison of the results of Examples 1-3 and Comparative Example 1 in Table 1, it can be seen that the adhesion of the copper layer of the composite current collectors of Examples 1-3 before and after being immersed in the electrolyte is much greater than that of Comparative Example 1, and after being immersed in the electrolyte, the adhesion of the copper layer of the composite current collectors of Examples 1-3 is only slightly reduced, while the copper layer of the composite current collector in Comparative Example 1 delaminates after being immersed in the electrolyte. This indicates that the polyurea resin coating of the embodiment of the present invention can greatly improve the bonding force between the copper layer and the PET film material in the composite current collector; and the polyurea resin coating has stable chemical properties and high resistance to acid, alkali, and electrolyte corrosion, so it can improve the stability of the composite current collector in the electrolyte, ensure that the composite current collector is immersed in the electrolyte for a long time, and there is still good bonding between the copper layer and the PET film material, and the copper layer does not peel off or fall off, thereby improving the service life of the composite current collector.

[0103] From the comparison of the results of Examples 1-3 and Comparative Example 1 in Table 1, it can be seen that the thermal shrinkage rates of the composite current collectors of Examples 1-3 are much smaller than those of Comparative Example 1, indicating that the polyurea resin coating of the embodiments of the present invention can greatly improve the heat resistance of the composite current collector, thereby preventing the heat generated during the use of the lithium-ion battery from damaging the structure of the composite current collector.

[0104] It can also be seen from the comparison of the results of Examples 1-3 and Comparative Example 1 in Table 1 that, under the same charge and discharge rate, when the battery capacity decays to 80%, the number of cycle cycles of the button half-cells assembled by the composite current collectors of Examples 1-3 is much greater than that of Comparative Example 1. This shows that the composite current collector with a polyurea resin coating in the embodiment of the present invention can greatly improve the cycle performance of lithium-ion batteries. This is because the polyurea resin coating greatly improves the heat resistance and electrolyte corrosion resistance of the composite current collector and the bonding force between the copper layer and the PET film in the composite current collector; and the coating formed by the polyurea resin is continuous and seamless, which can effectively prevent the acidic substances produced by the lithium-ion battery reaction from penetrating into the PET film, alleviate the corrosion of the electrolyte to the PET film, and avoid or at least alleviate the problems of shedding and aging that may occur in the existing composite current collector during long-term use, thereby improving the cycle performance and service life of the lithium-ion battery.

[0105] In summary, it can be concluded that the embodiment of the present invention can obtain a composite current collector with good mechanical properties, heat resistance, chemical stability, and bonding strength between the conductive layer and the polymer film material by coating the surface of the PET film material with a coating whose main component is a polyurea resin, and controlling the mass fraction ratio of the first component, the second component and the solvent of the synthetic polyurea resin within a certain range. Without significantly increasing the cost, the comprehensive performance of the composite current collector is improved, thereby improving the cycle performance and service life of the lithium-ion battery.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A polymer substrate for a composite current collector, characterized in that: The invention comprises a polymer film material and a coating, wherein the coating is arranged on at least one surface of the polymer film material, wherein the main component of the coating is a polyurea resin, wherein the polyurea resin is formed by reacting a first component and a second component in a solvent, wherein the main component of the first component is an isocyanate, and the main component of the second component is an amino compound, and the solvent is used to dissolve the first component and the second component, and the mass ratio of the first component, the second component and the solvent is 10 to 35:8 to 35:30 to 82.

2. The polymer substrate for composite current collector according to claim 1, characterized in that: The isocyanate includes one or more of diphenylmethane diisocyanate, toluene diisocyanate and polyether modified isocyanate; and / or, the amino compound includes one or more of polyether amine, polyester amine and modified amine compound; and / or, the solvent includes one or more of ethyl acetate, butyl acetate, dimethylformamide and toluene.

3. The polymer substrate for composite current collector according to claim 1, characterized in that: The mass ratio of the first component, the second component and the solvent is 25-35:23-35:30-52.

4. The polymer substrate for a composite current collector according to any one of claims 1 to 3, characterized in that: The solid content of the first component is 30% to 65%; and / or the solid content of the second component is 30% to 65%.

5. The polymer substrate for a composite current collector according to any one of claims 1 to 3, characterized in that: The thickness of the coating is 0.5 to 10 microns.

6. A method for preparing a polymer substrate for a composite current collector according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (S1), mixing the first component and the second component to obtain a mixture, and stirring the mixture at a high speed; Step (S2), adding the solvent to the mixed material, adjusting the solid content to 15% to 35%, and adjusting the viscosity to below 500 cps, to form a slurry; as well as Step (S3), coating the slurry on at least one surface of the polymer film material, and drying, to form the coating on at least one surface of the polymer film material.

7. The method for preparing a polymer substrate for a composite current collector according to claim 6, characterized in that: In the step (S1), during the high-speed stirring of the mixed material, the temperature of the mixed material and the stirring are controlled to be 10 to 35° C.; and / or the stirring time is 20 to 40 minutes.

8. A composite current collector comprising a polymer substrate and a conductive layer, characterized in that: The polymer substrate is the polymer substrate for a composite current collector described in any one of claims 1 to 5, or the polymer substrate for a composite current collector obtained by the preparation method in claim 6 or 7, and the conductive layer is arranged on the surface of the coating away from the polymer film material.

9. An electrode sheet, comprising a current collector and an electrode membrane, wherein the electrode membrane is arranged on the surface of the current collector, characterized in that: The current collector adopts the composite current collector as claimed in claim 8.

10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet and / or the negative electrode sheet adopts the electrode sheet as claimed in claim 9.